Reflections on the Medical Humanities Curriculum Design Based on "Comprehensive Health" and "Proactive Health": Oriented by Structural Competency - Yan SHI; Zhiguang DUAN (Yixue yu zhexue)
The content system of medical humanities curriculum urgently needs to be further expanded and deepened under the concepts of "comprehensive health" and "proactive health". However, the current topics of the medical humanities curriculum are still limited to the "doctor-patient" sphere and lack systematic attention to the macro-level structural factors underlying health issues, resulting in a structural disconnect between medical humanities education and the actual health needs of society. Based on an in-depth analysis of the status of medical humanities curriculum development, this paper systematically reviews the connotation of structural competency, and explores the necessity of integrating structural competency into the curriculum. Importantly, the study proposes pathways for structural competency curriculum design from seven dimensions: conceptual updates, faculty development, curriculum integration, interdisciplinary collaboration, teaching methods, practice-oriented approaches, and evaluation mechanisms. The study aims to provide a reference for deepening the reform of medical humanities education and to lay a solid foundation for cultivating high-quality healthcare professionals to support the Healthy China initiative.